PERAN MASJID SEBAGAI PUSAT INFORMASI DAN TEMPAT EVAKUASI SEMENTARA DALAM KESIAPASIAGAAN BENCANA GEMPABUMI DAN TSUNAMI KOTA PADANG - Algamar, Andree Harmadi; Bahar, Fauzi (Jurnal Manajemen Bencana (JMB), 2019)
Indonesia is located at the meeting point of three tectonics plate namely Indo-Australian plate, Eurasian, and the Pacific plate. This causes Indonesia has a high geological changes and more geological disasters. No exception for West Sumatra which has a watermelon fracture has a high risk of geological disasters such as earthquakes and tsunami. This threat can disrupt the social, economic and cultural life of Padang City community. Therefore, the government and the community need to make various preparedness efforts to reduce the risks caused by the earthquake and tsunami. It is necessary to know how far the potential of community can be utilized for disaster preparedness in Padang City especially as information center and shelter. The system of disaster information and shelter are two factors that can realize the system of preparedness to be effective. This research used qualitative research method and study using case based on happened in 2 research area. The aim is to analyze the role of the mosque as the center of information and location of shelter in handling the earthquake and tsunami disaster in Padang city as well as the factors that influence it. Some of the mosques in Padang City have been used in providing disaster information to community through various media such as board bulletins, face to face activity, distributing brochures or through loudspeakers. The mosque in Padang City has also become a shelter for evacuees. The factors that influence the mosque to function as a disaster information center and shelter location are the community feel safe and comfortable when they stayÂ  in the mosque, the trust of community on information from the mosque is very high, supporting facilities such as electricity, clean water, places of worship, place of negotiation, toilets and places rest for shelter, facilities and infrastructure as information center, the board of mosque who will manage the information a shelter and the policy of government of Padang City which support mosque as information center and shelter location.